OS MODELOS DE AVALIAÇÃO PARA CONCESSÕES RODOVIÁRIAS: UMA ANÁLISE CRÍTICA DOS PRINCIPAIS PARÂMETROS NAS RODOVIAS BRASILEIRAS - Silva, Fabiana Lopes da (2014)
This Dissertation aims to analyze the main parameters used in the modeling of financial structures that are used by the Federal Government, to estimate the rates of return of the roads to be granted in concession notices. The Federal Government establishes a series of assumptions to estimate that cost of capital in order to guide potential investors interested in the operation of highways to be granted. However, investors should base decisions from the opportunity costs incurred in the market environment, in line with the current macroeconomic situation above. There was an inadequate calibration of the main elements of the model to estimate the cost of capital, which adopts the CAPM (pricing model of capital assets), since it does not consider current market elements at the time of preparation of the notices. Such occurrences can distort the analysis of a possible interested in investments in road concessions, although there are many reasons, both doctrinal character, as a normative character, justifying the adoption of this model for the estimation of rates of return.